Korelasi Ekspresi VEGF dan Densitas Mikrovesel Dengan Respons Radioterapi Adenokarsinoma Serviks - Wibisono, Fennisia; Suryanti, Sri; Hernowo, Bethy S (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2014)
ABSTRACT Background: Most of cervical carcinoma patients, including cervical adenocarcinoma comes at an advanced stage and thus radiotherapy is one of the modality treatment. The success of radiotherapy depends on several prognostic factors such as the performance, staging, histopathology of tumor, presence of organ dysfunction and cellular biology marker such as VEGF. Activation singaling pathway Vascular Endothelial Growth Factor (VEGF) can induce radioresistance on cervical adenocarcinoma. Activation angiogenesis mediated by VEGF can be counted from microvessel density (MVD). Counting MVD use imunohistochemical CD34 on endothelial cells form capiller of blood vessel in peritumoral. The aim of this study was to determine correlation between immunohistochemistry VEGF dan MVD with neoadjuvant radiotherapy response cervical adenocarcinoma. Methods: This study was an observational study, cross-sectional and correlational analysis. Samples was collected by total sampling with amount 32 samples block parafin from Departement Anatomical Pathology General Hospital Dr. Hasan Sadikin Bandung and treated with complete neoadjuvant radiotherapy from Januari 2007 until December 2013. Immunohistochemical examination of VEGF and CD34 for counting MVD was done on all sample block parafin. Result: There was a strong correlation between microvessel density (MVD) with neoadjuvant radiotherapy response in cervical adenocarcinoma (p = 0.000). In this study MVD above 30 correlate with poor neoadjuvant radiotherapy response in cervical adenocarcinoma. Conclusion: Examination MVD recommended for cervical adenocarcinoma patient before radiation treatment. Keyword : Cervical Adenocarcinoma, CD34, Neoadjuvant Radiotherapy, VEGF